Analisis Kemampuan Ruang Terbuka Hijau dalam Mereduksi Konsentrasi CO2 dari Kontribusi Kendaraan Bermotor di Kampus USU Medan (Green Open Space Capability Analysis on Reducing Concentration of CO2 from Motor Vehicles at Campus USU Medan) - Irwansyah Banurea; Rahmawaty Rahmawaty; Yunus Afifuddin (Program studi Kehutanan USU, 2013)
Air pollution has become a serious problem in several major cities in Indonesia, especially Medan. Technological development in the field of transportation contribute to the increasing of energy necessaries, which eventually cause the increasing of energy’s residual that influence the air quality and potentially contaminate the environment. Campus USU as a renowned in Medan should be prepared as a role models to manage the existing condition of air pollution. For that, conducted research on existing vegetation in the campus USU in terms of the flow field emissions from motor vehicles which through the campus USU based on the traffic daily density. The collecting of vegetation data use the census method while for the daily traffic data used the traffic counting method. From the vegetation data will be computed extensive of canopy cover for each tree and will be multiplied by a factor of CO2 absorption coefficient in order to get the capability of vegetation to absorb the CO2 at campus USU. Then, from these capabilities will be obtained how emission levels that can not be absorbed by green open space. If the campus area is not able to reduce the emissions of existing discharge, then the control efforts by planting the trees in the campus area is needed. The research has been done about the existing vegetation in campus USU showed that there are 68 species with 3 types of deployment of green open space. The potential of CO2 absorption from 4.254 trees in the campus of USU Medan is 3327.25 kg / hr lower than the burden of emissions resulting from motor vehicle that is 6088.14 kg / hr. This absorption is not sufficient to reduce the burden of CO2 emissions resulting from motor vehicles. Keywords: Burden of CO2 Emissions, CO2 Absorbtion, Campus USU, Tree Species Distribution, Green Open Space